Disrupted thyroid hormone homeostasis in critical illness: clinical correlates and associations with hormone supplementation in a single-center retrospective observational study - Alicja Filipczyk; Szymon Zdanowski; Jan Kasprzyk; Karolina Niedzielska; Artur Rakhatsevich; Magdalena Anna Wujtewicz; Tomasz J. Stefaniak; Karol P. Steckiewicz (Anaesthesiology Intensive Therapy, 2026)
Background Thyroid hormone disturbances are a hallmark of critical illness and are commonly attributed to non-thyroidal illness syndrome. The clinical relevance of thyroid hormone supplementation in the intensive care unit (ICU) remains uncertain. This study aimed to characterize thyroid hormone concentrations in relation to disease severity in critically ill patients receiving thyroid hormone supplementation. Methods In this single-center retrospective study, data from 98 ICU patients receiving thyroid hormone supplementation were analyzed. A total of 186 measurements of thyroid-stimulating hormone (TSH), free triiodothyronine (fT3), and free thyroxine (fT4) were evaluated in relation to disease severity, organ dysfunction, and clinical interventions. Results Lower fT3 and fT4 concentrations were consistently associated with markers of critical illness, including shock, vasopressor use, mechanical ventilation, and higher SOFA scores. TSH showed weaker and less consistent associations but correlated positively with duration of ICU stay. Thyroid hormone concentrations were largely unrelated to most therapeutic interventions, with only weak correlations observed. Notably, hormone concentrations did not differ meaningfully between patients with and without preexisting thyroid disease, apart from higher TSH concentrations and levothyroxine dosing in the former group. Conclusions Thyroid hormone concentrations in critical illness were closely associated with disease severity. As all patients received supplementation and no comparator group was available, the independent effect of treatment could not be assessed. Prospective controlled studies are needed.